DISPARITAS SANKSI PIDANA PADA KASUS INVESTASI ILEGAL BERKEDOK USAHA HALAL (Studi Kasus Putusan PN No. 309/Pid.B/2018/PN Dpk dan No. 83/Pid.B/2018/PN Dpk) - Kadek Mei Eriani Putri; Ni Putu Ega Parwati; Kusuma, Putu Riski Ananda (Jurnal Ilmu Hukum Sui Generis, 2025)
The imposition of criminal sanctions against perpetrators of illegal investments in Indonesia still demonstrates inconsistencies, particularly when cases with similar modes of operation receive significantly different sentences. This research aims to analyze the disparity of criminal sanctions for perpetrators of illegal investments under the guise of halal businesses, through a case study of the District Court Decision Number: 309/Pid.B/2018/PN Dpk and Decision Number: 83/Pid.B/2018/PN Dpk. This study uses a normative legal research method with statutory, conceptual, historical, and case approaches. Data were collected through document studies of court decisions and relevant legal literature. The results indicate a significant disparity between the two rulings, even though the cases share similar modus operandi and impact. This disparity is caused by various factors, including the discretionary power of judges, subjective judicial considerations, and the absence of standardized sentencing guidelines. Therefore, an evaluation of the criminal justice system is necessary to ensure consistency and fairness in imposing sanctions on perpetrators of illegal investments.